Պետականաշինութեան հիմնախնդիրները ՀՀ գերագոյն խորհրդում 1990-1995ին - Զաքարեան, Լիլիթ (տպ. Atlas)
Based on the archival materials of the Armenian parliament and the publications of a number of outstanding actors of the time, the paper focuses on a very dramatic period of the modern history of the Republic of Armenia. It was a time of transition from being a part of the Soviet Union to becoming an independent state, a very complicated process indeed that spanned from 1990 to 1995. The paper highlights the diverse approaches and perceptions of the MPs concerning a set of topics which were matters of principle during that time.
Keywords: Պատմութիւն; Պետականաշինութիւն